PENGARUH STEREOTIP KRIMINALITAS TERHADAP INTERAKSI SOSIAL ANTARA MASYARAKAT SURABAYA DAN PERANTAU MADURA: (STUDI KASUS PADA ISU PENCURIAN KENDARAAN DI KOTA SURABAYA) - Dinar Mahkota Parameswari; Nikmah Suryandari (Universitas Islam Syekh Yusuf, 2025)
ABSTRACT? ? This research aims to analyze the influence of stereotypes of criminality on social interactions between the Surabaya community and Madurese migrants, focusing on motor vehicle theft cases in Surabaya City. The research method used a qualitative approach with a case study design, involving in-depth interviews with local people, Madurese migrants, and community leaders, as well as secondary data analysis from media coverage and related literature. The results showed that negative stereotypes of Madurese migrants were formed through media narratives and personal experiences, which then manifested in the form of discrimination, social segregation, and decreased intergroup trust. The tendency of Madurese migrants to form homogeneous groups as a response to prejudice actually widens social gaps and inhibits integration. This finding reinforces Bar-Tal's (1997) stereotyping theory and Goffman's (1963) stigma, while confirming the negative impact of generalization of criminality on social cohesion. This study recommends intercultural education, a more responsible role for the media, and inclusive policies to mitigate stereotypes and promote harmonious social interactions. ? Keywords : criminality stereotypes, social interaction, Surabaya society, Madurese migrants.